Analysis of book 4 in light of the requirements of the science, technology engineering, and mathematics (STEM) approach in the Kingdom of Saudi Arabia (build a suggested proposal) - Al-Otaibi, Maha Mohammed Shamroukh; Al-Harbi, Abdullah Awad Abdullah (Journal of Curriculum and Teaching Methodology, 2024)
The research aimed to identify the degree of availability of the requirements for the science, technology, engineering, and mathematics (STEM) curriculum in the Chemistry “4” textbook for the secondary stage in Saudi Arabia, prepare a list of the requirements for the STEM curriculum, and present a proposed scenario for developing a Chemistry “4” textbook in light of the requirements of the science and technology curriculum. STEM engineering and mathematics. The research adopted the descriptive method, using one of its types: It is (content analysis). The research sample is the student’s book “Chemistry 4” slated for the secondary stage, edition 1443 AH- 2021 AD. Among the most prominent results that study arrived at was the following: The degree of availability of the requirements of STEM curve was in the content of the book Chemistry “4” slated for the third grade. Secondary school with a grade of (intermediate) with an arithmetic average of (16.6%) for all academic units. The order of the units in terms of the degree of availability of main requirements for the STEM curriculum in Chemistry Book “4” scheduled for the third year of secondary school is as follows (sixth, fifth, first, second, third, Fourth), the requirement “Emphasizing twenty-first century skills.” came in first place with a (very high) degree in terms of the degree of availability in all units of the book, at a rate of (34.3%), and the requirement “focusing on integrated conceptual experience” came in second place. With a degree of (very high) in terms of the degree of availability in all units of the book, at a rate of (32.0%), the requirement to “include topics of contemporary technical sciences.” came in sixth and last place with a degree of (very low) in terms of the degree of availability in all units of book, with a rate of (3.4 %).
Keywords: STEM Curriculum; Content Analysis; Chemistry Book 4